2005
DOI: 10.1002/jbm.a.30311
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein kinase C in the monocyte‐derived macrophage‐mediated biodegradation of polycarbonate‐based polyurethanes

Abstract: Polycarbonate-polyurethanes (PCNUs) elicit a foreign body reaction during the initial tissue contact, partly mediated by the respiratory burst in monocytes, during which protein kinase C (PKC) activates NADPH (nicotinamide adenine dinucleotide phosphate) oxidase. Using an in vitro cell system, monocytes were differentiated into monocyte-derived macrophages (MDMs) and then reseeded onto three PCNUs (HDI431, HDI321, or MDI321): hexane (HDI) or 4,4-methylene bis-phenyl (MDI) diisocyanates synthesized with poly(1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 33 publications
5
23
0
Order By: Relevance
“…19 Another study of these PCNUs showed that MDM-mediated degradation of HDI431 was affected differently from the degradation of HDI321 (after the addition of the PKC inhibitor H-7). 25 These studies suggest that MDM can differentiate and react differently to material surfaces that have identical chemical moieties and differ by only 3% in hard segment concentration. 3 Therefore, although other studies have suggested that oxidation is the most dominant activity in the degradation of PUs, 38 this does not hold true for PUs in general and even for specific classes of PUs (i.e., polyetherPUs, PCNUs, etc.)…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…19 Another study of these PCNUs showed that MDM-mediated degradation of HDI431 was affected differently from the degradation of HDI321 (after the addition of the PKC inhibitor H-7). 25 These studies suggest that MDM can differentiate and react differently to material surfaces that have identical chemical moieties and differ by only 3% in hard segment concentration. 3 Therefore, although other studies have suggested that oxidation is the most dominant activity in the degradation of PUs, 38 this does not hold true for PUs in general and even for specific classes of PUs (i.e., polyetherPUs, PCNUs, etc.)…”
Section: Discussionmentioning
confidence: 97%
“…Previously, oxidation of a PCNU by H 2 O 2 pretreatment did show changes in its susceptibility to hydrolytic cleavage by CXE. 25 Since neutrophils, monocytes, and MDM all release ROS it is possible in vivo for MDM to attach to an implanted material that has previously been oxidized. There were significant differences in the response of the MDM adherent to the oxidized PCNUs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations